IMPLEMENTASI PENINGKATAN KUALITAS CRUMB RUBBER MENGGUNAKAN METODE PDCA DI PT. RHL - Vera Devani; Teti Alawiyah (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
PT. RHL is a foreign private company that manufactures crumb rubber with Indonesian Rubber Standard (SIR) 20, which is natural rubber which will be further processed into finished rubber goods, such as tires and other rubber products. The method used in this study is the PDCA (Plan-Do-Check-Action) Method which is one of the methods in Quality Control that is used to test and implement changes that occur so that improvements can be made in the performance of products, processes and systems in the future. The purpose of this study is to determine the type of disability that becomes the priority of repair, determine the causes of product defects and determine the actions that must be taken by the company. Based on the results of research conducted, it can be concluded that the type of defect that is a priority for improvement is white spot defects and out space lab. The main causes of these defects are operator errors and errors of lab employees. Actions taken to reduce white spot defects and out of space labs include the head production holding training, supervision and direction and rolling work for the operator, the maintenance department doing regular maintenance on the machine, as well as checking raw materials. Keyword: PDCA (plan-do-check-action), new seven tools , quality control, seven tools